Pengelolaan Hubungan Antarpribadi Pada Pasangan Berpacaran Long Distance Relationship (LDR) Untuk Pengembangan Hubungan Berkomitmen Serius - Fatraya, Denisa; Noor Rakhmad, M.I.KOm, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
LDR relationship is prone to conflict and separation. Frequent conflicts due to poor communication such as low intensity and frequency of communication, misunderstandings, unresolved conflicts, high suspicion, spouse bustling, low confidence in spouses, fewer meetings with partners. But there is a long-distance relationship and stay afloat until so long can even commit seriously with his partner. This study uses the theory of relational dialectics theory (RDT) or dialectical theory of relationship as the main theory, as well as privacy management theory, social penetration theory and model of relationship development as a supporting theory. These theories to explain the management of communication on long-distance relationships to be able to commit seriously. The results of research that is managed in the development of interpersonal communication relationship is the feeling of mutual love and love that underlies them to continue to survive long distance relationships that are vulnerable by conflict and the breakdown of relationships. it is marked by how often they express their feelings to their partner. And the mutual trust and understanding of each other and open to the couple to be a supporting factor to deliver the relationship to a serious stage. The next result is how the management of communication in interpersonal communication to develop the relationship to the stage of serious commitment is the existence of self-disclosure of the couple as told about the problems experienced even the privacy of the couple, find out the things favored and disliked partner, explain to the couple what is meant when misunderstanding occurs. Informants share private information with a partner who is a higher stage in the relationship because they already trust and comfortably share the story with their partner. These are the ways in which they manage communication so that relationships can develop more intimately.